Strategy to Improve Employee Performance Through Strengthening Empowerment, Teamwork and Job Satisfaction : Empirical Study Using Survey Method and Path Analysis Technique on Employees of Bogor City Environmental Service - Nanan Triyani; Widodo Sunaryo; Nancy Yusnita (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
The purpose of this study was to determine the Strategy for Improving Employee Performance through Strengthening Empowerment, Teamwork and Job Satisfaction at the Bogor City Environmental Service. The study population was 280 people with a sample size of 165 people calculated using the Slovin formula. Data collection for each variable studied using a questionnaire with a rating scale. Data analysis techniques using descriptive statistical analysis techniques and path analysis techniques. The results showed (a) there is a positive direct effect of empowerment on job satisfaction, with a path coefficient value of βzx1 = 0.155, a t-value of 1.998> t table value of 1.654 (b) there is a positive direct effect of teamwork on job satisfaction, with a path coefficient value of βzx2 = 0.415, and a t-value of 5. 167> t table value of 1.654 (c) there is a positive direct effect of job satisfaction on performance, with a path coefficient value of βzy 415, and a calculated t-value of 5.167 > t table value of 1.654 (c) there is a positive direct effect of job satisfaction on performance, with a path coefficient value of βzy 209, and a calculated t-value of 2.722 > t table value of 1.654. (d) there is a positive direct effect of empowerment on performance, with a path coefficient value of βyx1 = 0.470, and a calculated t value of 4.149 > t table value of 1.654. (e) there is a positive direct effect of teamwork on performance, with a path coefficient value of βyx2 = 0.466, and a calculated t value of 5.599> t table value of 1.654. (f) there is a positive indirect effect of empowerment on performance through job satisfaction, with a regression coefficient value of 0.891 and 0.238, and from the calculation of the Sobel test, the z-count value is 10.241> 1.96. (g) there is a positive indirect effect of teamwork on performance through job satisfaction, with a coefficient value of 0.706 and 0.238 and from the calculation of the Sobel test, the z-count value is 8.115> z-table 1.96. Thus, it can be concluded that by strengthening empowerment, teamwork and job satisfaction, employee performance in the organization can be improved.